PENGAMATAN JENIS GLIKOKONYUGAT PADA SEL KELENJAR MANDIBULA BABI MENGGUNAKAN TEKNIK HISTOKIMIA LEKTIN - Heryani, Luh Gde Sri Surya; Suarsana, I Nyoman (Buletin Veteriner Udayana, 2012)
Study of glycoconjugates in the mandibular gland of swine was performed. The aim of thisstudy was to identify the composition of mainly terminal carbohydrate residues ofglycoconjugates in the mandibular gland of swine using Alcian Blue (AB), Periodic AcidSchiff (PAS) and lectin histochemistry staining methods. Results showed that neutralcarbohydrates were detected in the mandibular gland ie. mucous cells, serous cells, epithelductus and lumen ductus cells. Acidic carbohydrates were detected in sereus cells of thegland. Whereas in the mucous cells, epitel ductus and lumen ductus cells there were noacidic carbohydrates detected. Using six types of lectins ie: PNA, RCA, WGA, LCA, ConAand UEA the terminal carbohydrate residues detected in the mucous cells of the gland weregalactose, GlcNAc, GalNAc, sialic acid and fructose. In the epitel ductus cellscarbohydrates detected were galactose, GalNAc, sialic acid, fucose and manose,respectivelly.
Keywords: glycoconjugate, mandibular gland of pig, lectin histochemistry